Kampo Medicine: Evaluation of the Pharmacological Activity of 121 Herbal Drugs on GABAA and 5-HT3A Receptors - Hoffmann, Katrin M.; Herbrechter, Robin; Ziemba, Paul M.; Lepke, Peter; Beltrán, Leopoldo; Hatt, Hanns; Werner, Markus; Gisselmann, Günter (Frontiers in Pharmacology, 2016)
Kampo medicine is a form of Japanese phytotherapy originating from traditional Chinese medicine (TCM). During the last several decades, much attention has been paid to the pharmacological effects of these medical plants and its constituents. However, in many cases, a systematic screening of Kampo remedies to determine pharmacologically relevant targets is still lacking. In this study, we performed a broad screening of Kampo remedies to look for pharmacologically relevant 5 HT3A and GABA(A) receptor ligands. Several of the Kampo remedies are currently used for symptoms such as nausea, emesis, gastrointestinal motility disorders, anxiety, restlessness or insomnia. Therefore, we analyzed the pharmacological effects of 121 herbal drugs from Kampo medicine as ethanol tinctures on heterologously expressed 5 HT3A and GABA(A) receptors, due to the involvement of these receptors in such pathophysiological processes. The tinctures of Lindera aggregata (radix) and Leonurus japonicus (herba) were the most effective inhibitory compounds on the 5 HT3A receptor. Further investigation of known ingredients in these compounds led to the identification of leonurine from Leonurus as a new natural 5 HT3A receptor antagonist. We also identified several potentiating herbs (e.g., Magnolia officinalis (cortex), Syzygium aromaticum (flos) and Panax ginseng (radix)) for the GABAA receptor, which are all traditionally used for their sedative or anxiolytic effects. A variety of tinctures with antagonistic effects, for instance Salvia miltiorrhiza (radix) were also detected. Therefore, this study reveals new insights into the pharmacological action of a broad spectrum of herbal drugs from Kampo, allowing a better understanding of their physiological effects and clinical applications.